STREET VENDORS’ PERSPECTIVE ON THE STREET VENDING BUSINESS - MAHADEVAN, Dr. M. (International Journal of Advanced Science and Technology, 2019)
The highest Indian Constitutional Document provides equality for all human beings with dignity, but it is not seen in the case of this workforce. They face a threat from the giant Indian and Multinational Companies in the name of globalization. Many retail outlets are coming to compete in this poor helpless workforce. Therefore, to studying the street vendors’ perspective on the street vending business is so significant. The study found that a vast majority of the respondents (73.6 per cent) had invested an amount below Rs.1000, 37 per cent of the sample street vendors’ net average daily earnings was between Rs.201 to Rs.300, a majority of the sample respondents (58.8 per cent) adopted bargaining pricing strategy and a vast majority of the street vendors (74.2 per cent) were self-employed and carried out their business independently in the study area of Madurai city.